Clinical and haematological responses of feline blood donors anaesthetised with a tiletamine and zolazepam combination. Issue 4 (April 2015) - Spada, Eva; Proverbio, Daniela; Bagnagatti De Giorgi, Giada; Perego, Roberta; Valena, Emanuela; Della Pepa, Alessandra; Baggiani, Luciana
This prospective study investigated the effect on clinical and haematological variables of the anaesthetic combination of tiletamine and zolazepam in feline blood donors. Blood (10 ml/kg bodyweight to a maximum volume of 60 ml) was collected from the jugular vein of 31 owned healthy cats anaesthetised with 2.5 mg/kg of tiletamine and 2.5 mg/kg of zolazepam intramuscularly. Rectal temperature (RT), systolic arterial pressure (SAP), mean arterial pressure (MAP), diastolic arterial pressure (DAP), heart rate (HR) and complete blood count (including red blood cells [RBC], haemoglobin [HB], haematocrit [HT], platelet [PLT] count, white blood cells [WBC], lymphocytes, neutrophils, eosinophils, monocytes and basophils) were evaluated pre- and postdonation. RT decreased significantly ( P <0.01) after blood donation (mean change in RT −0.7°C). Significant increases in SAP ( P = 0.03), MAP ( P <0.01) and DAP ( P <0.01) occurred after blood donation (mean increase 13 mmHg, 12 mmHg and 11 mmHg, respectively). Although RBC, HT, HB, WBC, PLT, neutrophil and monocyte counts decreased, and HR, and lymphocyte, eosinophil and basophil counts increased after blood donation this change was not statistically significant. Mean time from pre- to postdonation evaluation was 39 ± 11 mins (range 24–76 mins). None of the cats had evidence of pallor or collapse after recovery from anaesthesia. The collection of blood at 10 ml/kg bodyweight to a maximum volume of 60 ml in healthy cats using a low dose tiletamine and zolazepam anaesthetic appears to be well tolerated by feline blood donors.